2006
DOI: 10.1073/pnas.0604883103
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory utilization of genetic redundancy through responsive backup circuits

Abstract: Functional redundancies, generated by gene duplications, are highly widespread throughout all known genomes. One consequence of these redundancies is a tremendous increase to the robustness of organisms to mutations and other stresses. Yet, this very robustness also renders redundancy evolutionarily unstable, and it is, thus, predicted to have only a transient lifetime. In contrast, numerous reports describe instances of functional overlaps that have been conserved throughout extended evolutionary periods. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
174
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(177 citation statements)
references
References 71 publications
3
174
0
Order By: Relevance
“…The transcript of this gene was constitutively high and not affected much by heat stress. On the other hand, it also is the case that functional redundancy has been observed in most gene families in spite of expressional diversification (Kafri et al 2006). In Arabidopsis chloroplast localized two Hsp70 proteins show differential transcript expression.…”
Section: Discussionmentioning
confidence: 96%
“…The transcript of this gene was constitutively high and not affected much by heat stress. On the other hand, it also is the case that functional redundancy has been observed in most gene families in spite of expressional diversification (Kafri et al 2006). In Arabidopsis chloroplast localized two Hsp70 proteins show differential transcript expression.…”
Section: Discussionmentioning
confidence: 96%
“…It was suggested that gene duplicates that are consistently coexpressed are unlikely to have redundant functions (4,22). The rationale is that systematically coregulated duplicate genes may be simultaneously required for a given functionality and therefore cannot substitute for each other's absence.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these pieces of evidence suggest that, in particular types of systems, genetic redundancy may play an as-yetunidentified role that could provide a basis for its extended conservation. Although it is unlikely that functional overlaps have been conserved solely for the sake of buffering the mutations (8,19,20), the possibility that they could be advantageously used for a range of different functionalities is intriguing (4,6). If such functionalities do exist, they pose two evolutionary questions.…”
mentioning
confidence: 99%
“…While finding the optimal input distribution and the corresponding maximal information I is difficult in general, in the case of small noise, σ g ≪ 1, we previously derived a simple formula for the capacity [8]: (36) where (37) (38) and σ c is given either by Eq. (9) for the case of direct transcriptional regulation, or by Eq.…”
Section: Comparing Optimal Information Flow In the Two Schemesmentioning
confidence: 99%
“…Several averaging strategies that make transcriptional regulation more reliable have been identified: there is averaging over time as molecules accumulate [2,28,[31][32][33][34], averaging over expression levels of multiple genes that are regulated by the same TF [16,17,38,39], and averaging over space as molecules diffuse between neighboring cells or nuclei, e.g., in a developing embryo [19,[40][41][42][43] or organoid [44]. In the (typical) case where one TF targets multiple genes, there is a regime where information transmission is optimized by complete redundancy in the response of these targets, and another regime in which the concentrations for activation or repression of the targets are staggered so as to "tile" the dynamic range of inputs [16,17].…”
Section: Introductionmentioning
confidence: 99%